Significance of Paroxysmal Atrial Fibrillation Complicating Acute Myocardial Infarction in the Thrombolytic Era - Michael Eldar; M Canetti; Zeev Rotstein; Valentina Boyko; Shmuel Gottlieb; Elieser Kaplinsky; Solomon Behar (1998)
Background —Paroxysmal atrial fibrillation (PAF) is considered a frequent complication of acute myocardial infarction (AMI), associated with increased in-hospital and long-term mortality rates. This notion is based on data collected before thrombolysis and additional modern methods of treatment became widely available, and no information is available on the significance of PAF in the general population with AMI in the thrombolytic era. The aim of the present study was to define the incidence, associated clinical parameters, and short- and long-term prognostic significance of PAF in patients with AMI in the thrombolytic era. Methods and Results —A prospective, nationwide survey was conducted of 2866 consecutive patients admitted with AMI in all 25 coronary care units in Israel during January/February 1992, 1994, and 1996 (thrombolytic era [TE]). The data were compared with a previous Israeli study of 5803 patients with AMI hospitalized in 1981 through 1983 (prethrombolytic era [PTE]). Patients in the TE with PAF were older and had a worse risk profile than those without PAF. PAF in the TE was independently associated with increased 30-day (odds ratio, 1.32; 95% confidence interval, 0.92 to 1.87) and 1-year (relative risk, 1.33; 95% confidence interval, 1.05 to 1.68) mortality rates. The incidence of PAF (8.9% and 9.9%) and the 30-day (25.1% and 27.6%) and 1-year (38.4% and 42.5%) mortality rates of patients with PAF were similar in the TE and PTE, although PAF in the TE occurred in older and sicker patients than those in the PTE. After adjustment for conventional risk factors, PAF was associated with significantly lower 30-day (odds ratio, 0.64; 95% confidence interval, 0.44 to 0.94) and 1-year (relative risk, 0.69; 95% confidence interval, 0.54 to 0.88) mortality rates compared with the PTE. Conclusions —Patients with AMI who develop PAF in the TE have significantly worse short- and long-term prognoses than patients without PAF, mostly due to their worse risk profile. After adjustment for confounding factors, patients with PAF in the TE have a better overall outcome than counterparts in the PTE, probably reflecting the better management of patients with AMI in the TE.